2011
DOI: 10.1007/s12663-011-0324-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal Derangement of Temporomandibular Joint: An Evaluation of Effect of Corticosteroid Injection Compared with Injection of Sodium Hyaluronate after Arthrocentesis

Abstract: Aims and Objectives Internal derangements are the commonest disorders of temporomandibular joint (TMJ). Different treatment modalities including conservative and surgical methods have been proposed to treat the same. Arthrocentesis is gaining popularity in the treatment of internal derangement of TMJ. Being minimally invasive it does not have the demerits of surgical approaches and at the same time is producing better results than conservative approaches. This study evaluates and compares corticosteroid and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 19 publications
6
33
0
7
Order By: Relevance
“…In the current literature, there are several studies that have compared the outcome of the use of hyaluronic acid and corticosteroids [16,[28][29][30][31][32], but very few have focused on the benefits of the use of platelet-rich plasma [33][34][35]. To the authors' knowledge, there is no research currently available that compares the use of these three products in TMJ arthralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, there are several studies that have compared the outcome of the use of hyaluronic acid and corticosteroids [16,[28][29][30][31][32], but very few have focused on the benefits of the use of platelet-rich plasma [33][34][35]. To the authors' knowledge, there is no research currently available that compares the use of these three products in TMJ arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, as demonstrated in several previous studies, the use of bite splint shows a high efficacy [36], as well as the use of intra-articular infiltrations of betamethasone, hyaluronic acid and platelet-rich plasma [28,29,[31][32][33][34][35]37,38]. However, most of the studies associate them with more invasive procedures, such as arthrocentesis that is very effective in the TMJDs and can be performed on an outpatient basis under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies with different follow-up periods have shown that a single arthrocentesis procedure results in a decrease in pain ranging from 37 to 86%. 3,31,36,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] These studies generally involve heterogeneous populations and most inject HA or CS as part of the procedure. These studies are not double blinded and most are not randomized, which introduces potential bias and confounders.…”
Section: Discussionmentioning
confidence: 99%
“…They are used in multiple joints for inflammatory arthropathy, including the TMJ. 32,[42][43][44][45] When comparing HA with CS, some investigators have found them equally effective, 42,45 whereas others have found HA to be superior. 32 The relative lack of evidence supporting or refuting the use of HA or CS makes recommending either problematic.…”
mentioning
confidence: 99%
“…13 Intra-articular corticosteroid injection alone or after arthrocentesis provides, long-term palliative effects on subjective symptoms and clinical signs of TMJ pain. 14,15 The anti-inflammatory effects of intra-articular corticosteroids on synovial tissues have been well documented.…”
Section: Discussionmentioning
confidence: 99%